Mobile application learning programme to learn fundamental of data structure using Gagne's learning style / Muhammad Syafiq Izzuddin Bahrin - Muhammad Syafiq Izzuddin Bahrin (2017)
Nowadays, the need to implement multimedia in education is becoming more important. It is also seen as an effective way for learning and teaching. Besides, most of the studies declared that a major drawback for beginner programmer is having weak skills on planning and outline This android-based mobile application is design for learners who want to learn about fundamental ofdata structure especially for Computer Science students. Topics covered in this mobile apps are Array list, Linked List, Queue and Stack. This development creates On-The- Go learning. It is also can be use as lecture note since the contents in this mobile app follows syllabus in CSC438. To develop this mobile apps, a research methodology is being applied which consists of analysis phase, design phase, develop phase, implement phase and evaluate phase. During design, Gagne's learning theory was implemented to enhanced the effectiveness of learning. As for development of this application, Android Studio tool has been used while the programming language involved will be JAVA.